2011
DOI: 10.1007/s11207-011-9801-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Solar and Geomagnetic Activity Indices, and Their Relationship: 1960 – 2001

Abstract: We employ annually averaged solar and geomagnetic activity indices for the period 1960 -2001 to analyze the relationship between different measures of solar activity as well as the relationship between solar activity and various aspects of geomagnetic activity. In particular, to quantify the solar activity we use the sunspot number R s , group sunspot number R g , cumulative sunspot area Cum, solar radio flux F 10.7, and interplanetary magnetic field strength IMF. For the geomagnetic activity we employ global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…A good correspondence between the aa index and the number of days per year with a solar wind speed higher than 500 km s −1 has been reported (Echer et al, 2004). Verbanac et al (2011) noted that the evolution of the Ap and Dst (sensitive to storm-time disturbances) indices correlates best with the interplanetary magnetic field (IMF) variations, which strongly affect the ring current evolution (Echer et al, 2008).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A good correspondence between the aa index and the number of days per year with a solar wind speed higher than 500 km s −1 has been reported (Echer et al, 2004). Verbanac et al (2011) noted that the evolution of the Ap and Dst (sensitive to storm-time disturbances) indices correlates best with the interplanetary magnetic field (IMF) variations, which strongly affect the ring current evolution (Echer et al, 2008).…”
Section: Discussionmentioning
confidence: 84%
“…For example, aa and Ap indices have been found to correlate with the sunspot number with roughly a 2-year time lag (Echer et al, 2004;Verbanac et al, 2011). A good correspondence between the aa index and the number of days per year with a solar wind speed higher than 500 km s −1 has been reported (Echer et al, 2004).…”
Section: Discussionmentioning
confidence: 88%
“…Takalo and Mursula (2020) and Takalo (2020b) have also shown that the larger the sunspot groups the more clearly their overall distribution during the solar cycle is double-peaked. Verbanac et al (2011) analyzed the correlation (during 1960 -2001) of several solaractivity indices: sunspot number, group sunspot number, cumulative sunspot area, solar radio flux F 10.7 , and interplanetary magnetic field strength (IMF) with geomagnetic activity indices: Ap, Dst, and Dcx, and the regional geomagnetic index RES, specifically estimated for the European region. The geomagnetic indices Ap, Dcx, Dst, and RES are all well correlated with the considered solar indices.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [11] analyzed correlations between yearly mean solar indices (sunspot number, group sunspot number, and cumulative sunspot area) and geomagnetic indices (Ap and Dst) between 1960 and 2001. They reported the correlation coefficient of sunspot numbers with Ap and Dst as follows: 0.55 with a time delay of 2 years, and -0.59 with no delay, successively.…”
Section: Resultsmentioning
confidence: 99%